The Relevance of the Hadith 'A Woman is Married for Four Things' in Contemporary Muslim Mate Selection: A Maudhu'i Approach - Ghina Sofia Mahfuzah; Hairul Hudaya; Salma Ellya (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
ENGLISH: The Relevance of the Hadith 'A Woman is Married for Four Things' in Contemporary Muslim Mate Selection: A Maudhu'i ApproachObjective: This study aims to analyze the hadith “Women Are Married for Four Reasons” using a thematic approach and examine its relevance in the choice of a spouse in contemporary Muslim society. Method: This study uses a Maudhui approach, collecting related hadiths, analyzing their sanad and matan, and exploring the social context behind the hadith. Results: Although wealth, lineage, and beauty are essential, religion should be the top priority in choosing a spouse because religion is directly related to happiness and stability in the household. In addition, choosing a spouse based on religion is not only a matter of spirituality, but also of morals, emotional maturity, and readiness to build a household. Conclusion: The Maudhui approach offers a more comprehensive understanding of the message of the hadith for fostering a harmonious and sustainable Muslim family. Contribution: This research provides new insights into understanding the message of the hadith “Women are married for four reasons,” as well as its relevance in the social and cultural context of contemporary Muslim society.INDONESIAN: Relevansi Hadis “Wanita Dinikahi Karena Empat Perkara” dalam Pemilihan Pasangan Muslim Kontemporer: Sebuah Pendekatan Maudhui.Tujuan: Penelitian ini bertujuan untuk menganalisis hadis